Retraction Note: Children’s physical activity level and sedentary behaviour in Norwegian early childhood education and care: effects of a staff-led cluster-randomised controlled trial - Eivind Andersen; Steinar Øvreås; Kari Anne Jørgensen; Janne Borch-Jenssen; Thomas Moser (BMC Public Health, 2024)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12889-024-18629-0.